2015
DOI: 10.1007/s10658-015-0690-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic approaches for mitigating losses caused by bacterial wilt of tomato in tropical islands

Abstract: Bacterial wilt, caused by Ralstonia solanacearum (Smith, US Department of Agriculture, 12, 1-28, 1986) Yabuuchi et al. (Microbiology and Immunology, 39, 897-904, 1995) (formerly Pseudomonas solanacearum), causes 35-90 % yield loss in tomato production in hot-humid tropical regions. Commonly used strategies for minimizing incidence of bacterial wilt include choosing resistant varieties, cocopith based growing media, chemical methods, grafting on resistant rootstocks, application of biocontrol agents and fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 78 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…This might be due to the poor colonization ability of antagonistic strains under different field conditions. The performance of BCAs is hindered by some difficulties, which are associated with the production, storage, and subsequent application of BCAs (Singh et al, 2015;Yuliar et al, 2015). Many previous studies reported that bacterial wilt was suppressed by organic matter.…”
Section: Most Researchers Are Interested In Developing Biologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to the poor colonization ability of antagonistic strains under different field conditions. The performance of BCAs is hindered by some difficulties, which are associated with the production, storage, and subsequent application of BCAs (Singh et al, 2015;Yuliar et al, 2015). Many previous studies reported that bacterial wilt was suppressed by organic matter.…”
Section: Most Researchers Are Interested In Developing Biologicalmentioning
confidence: 99%
“…It can grow endophytically and survive in soil, and it has a wide host range and biodiversity (Singh et al, 2015;Yuliar et al, 2015). To control bacterial wilt disease, different methods have been precribed till date (Yuliar et al, 2015).…”
mentioning
confidence: 99%
“…However, this topic still remains in its infancy in plant disease. Ralstonia solanacearum and Fusarium oxysporum, bacterial and fungal plant pathogens that cause wilt disease, can lead to yield losses up to 90% [11] and 80%, respectively, in a wide range of hosts [12,13]. While these pathogens have been studied in single pathogen-host systems, consequences of mixed infections are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial wilt, which is caused by the soilborne pathogenic bacterium Ralstonia solanacearum, is a serious and widespread disease that affects tomato production throughout the world [2][3][4]. R. solanacearum typically invades plants through the root wounds, colonizes host plant xylem vessels, and causes yield losses for 35-90% [5]. Bacterial wilt is managed with synthetic fungicides and by breeding resistant cultivars [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%